RETRACTED: Modern approach in railcar fleet management - Pokrovskaya O.D.; Nikiforova G.I.; Nikiforov V.V.; Pankrateva G.I. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001